2014
DOI: 10.12659/ajcr.889955
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C- and HIV-induced porphyria cutanea tarda

Abstract: Patient: Male, 47Final Diagnosis: Porphyria cutanea tardaSymptoms: Chills • cough dry • thumb swellingMedication: —Clinical Procedure: —Specialty: Metabolic Disorders and DiabeticsObjective:Challenging differential diagnosisBackground:Porphyria cutanea tarda (PCT) is the most common type of the porphyria. It occurs due to the deficiency of enzyme uroporphyrinogen decarboxylase (UROD), which is the fifth enzyme in the biosynthesis of heme and catalyzes the conversion of uroporphyrinogen to coproporphyrinogen. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…It is important to note that Porphyrias are multifactorial diseases, and that PCT in particular can be triggered by alcoholism, estrogens, drug abuse, iron overload or hepatotropic viral infections, through different mechanisms of alterations of heme metabolism ( 2 , 4 , 12 , 13 ). In our previous studies ( 12 ) and in those from other authors ( 40 , 41 ), the clinical symptomatology and biochemical alterations commonly observed in PCT patients are similar to those seen in HIV patients who develop PCT. Moreover, no differences were observed in terms of response to treatments for PCT (hydroxychloroquine alone or combined with phlebotomies).…”
Section: Discussionsupporting
confidence: 82%
“…It is important to note that Porphyrias are multifactorial diseases, and that PCT in particular can be triggered by alcoholism, estrogens, drug abuse, iron overload or hepatotropic viral infections, through different mechanisms of alterations of heme metabolism ( 2 , 4 , 12 , 13 ). In our previous studies ( 12 ) and in those from other authors ( 40 , 41 ), the clinical symptomatology and biochemical alterations commonly observed in PCT patients are similar to those seen in HIV patients who develop PCT. Moreover, no differences were observed in terms of response to treatments for PCT (hydroxychloroquine alone or combined with phlebotomies).…”
Section: Discussionsupporting
confidence: 82%
“…The diagnosis of PCT can be confirmed by high serum porphyrins, increased excretion of urinary uroporphyrin, and fecal coproporphyrin and isocoproporphyrin. 15 Normally, only trace amounts of porphyrins are present in plasma, and the amounts increase markedly in patients with cutaneous porphyrias. Being both sensitive and specific, it is increased in any patient with skin problems related to any type of porphyria and is seldom increased in other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…If serum porphyrins are negative, porphyrias as a cause of the blistering condition can be ruled out. 15…”
Section: Discussionmentioning
confidence: 99%
“…PCT, which is classified into sporadic and hereditary types, is also characterized by skin lesions in sun-exposed areas and liver dysfunction, as in EPP. A number of factors, such as alcohol ( 15 ), hepatitis C virus infection ( 16 ), HIV infection ( 16 , 17 ), estrogen exposure ( 18 ), renal failure ( 19 ), and lymphoma ( 20 ), have been identified as potential triggers for sporadic PCT. However, in contrast to EPP, PCT is characterized by iron overloading, which partially explains the liver dysfunction in this type of erythropoietic porphyria.…”
Section: Discussionmentioning
confidence: 99%